Studi Kelayakan Pengembangan Air Minum di Zona 2 Kota Tangerang 2016-2021 (Feasibility Study on Drinking Water Development in Zone 2 Tangerang City 2016-2021) - Rully Angraeni Safitri; Muhammad Ali Mu’min (Universitas Muhammadiyah Tangerang, 2020)
Drinking water is one of the basic human needs, so important that the 1945 Constitution in Palas 33 Paragraph 3 regulates the maximum use of water for the prosperity of the Indonesian people. Access to drinking water which is the MDG's target is 68.87% of the Indonesian peopleserved access to safe drinking water in 2015, currently it has not been achieved.rPIJMN plans that 100% of Indonesians will get access to drinking water by 2019. To achieve this target requires an additional production capacity and a large enough distribution network. it is necessary to build infrastructure that can support the increasing need for drinking water.One of the ways to develop infrastructure to support public access to drinking water can be done through a funding investment strategy by encouraging private and banking participation, and other non-government sources of funds in SPAM development. In carrying out this investment in SPAM development, it is necessary to strengthen human resources and institutions in the regions, including the PDAM, to understand the feasibility and financial impact of the PDAM. a feasibility analysis model is needed and financial risk along with other risks in the SPAM Development Concession Cooperation.(Air minum merupakan salah satu kebutuhan dasar manusia, sedemikian pentingnya sehingga Undang-Undang Dasar 1945 dalam Palas 33 Ayat 3 mengatur pemanfaatan air sebesar-besarnya untuk kemakmuran rakyat Indonesia.Akses air minum yang menjadi target MDG’s yaitu 68,87% masyarakat Indonesia dapat terlayani akses air minum aman pada tahun 2015, saat ini belum tercapai. RPIJMN merencanakan 100% masyarakat Indonesia mendapatkan akses air minum pada tahun 2019. Untuk mencapai target tersebut dibutuhkan penambahan kapasitas produksi dan penambahan jaringan distribusi yang cukup besar. Perlu dibangun infrastruktur yang dapat menunjang peningkatan kebutuhan air minum tersebut. Pembangunan infrastruktur untuk menunjang peningkatan akses masyarakat terhadap air minum dapat dilakukan salah satunya melalui strategi investasI pendanaan dengan mendorong partisipasi swasta dan perbankan, dan sumber dana non Pemerintah lainnya dalam pengembangan SPAM. Dalam melaksanakan investasi pengembangan SPAM ini diperlukan perkuatan SDM dan kelembagaan di daerah termasuk PDAM untuk memahami kelayakan dan pengaruhnya terhadap finansial PDAM. Diperlukan suatu model penyusunan analisa kelayakan dan risiko keuangan beserta risiko-risiko lainnya pada Kerjasama Pengusahaan Pengembangan SPAM.)